The virtual platforms of the social economy and the collaborative economy: one more possibility of access to housing and development of SDGs 8, 11 and 12 intimes of COVID-19 - CANALES GUTIÉRREZ, Silvana (Revista Jurídica Portucalense, 2022)
In times of COVID-19, where it is more difficult to envision a stable and sustainable society, the possibility of creating, using and promoting virtual platforms that fulfill their tasks under the spectrum of the social economy in parallel with collaborative economy platforms that meet market economy criteria is increasingly tangible. The foregoing implies that digital platforms can have objectives that transcend the profit motive and can develop their activities taking into account social values ​​that would be summarized in the general interest. Specifically, and related to the Sustainable Development Goals (SDG), we consider that the use of digital platforms in some cases can help meet some SDGs: Ensure sustainable consumption and production patterns (12 SDGs); promote sustained, inclusive and sustainable economic growth, employment and decent work for all (8 SDGs) and Make cities inclusive, safe, resilient and sustainable (11 SDGs).